Utilizing decision support systems for strategic public policy planning - Timoulali, Mohamed 1951 (Advances in public policy and administration (APPA) book series, 2020)
"This book explores the design and implementation of decision-making support systems for the planning, monitoring, and evaluation of public policies in the context of sustainable development"